2003
DOI: 10.1162/089892903322598166
|View full text |Cite
|
Sign up to set email alerts
|

A Monotonic Code for Sound Azimuth in Primate Inferior Colliculus

Abstract: Abstract& We investigated the format of the code for sound location in the inferior colliculi of three awake monkeys (Macaca mulatta). We found that roughly half of our sample of 99 neurons was sensitive to the free-field locations of broadband noise presented in the frontal hemisphere. Such neurons nearly always responded monotonically as a function of sound azimuth, with stronger responses for more contralateral sound locations. Few, if any, neurons had circumscribed receptive fields. Spatial sensitivity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 72 publications
11
41
1
Order By: Relevance
“…Neurons responsive only to high frequencies were too rare (one neuron) to include as a separate category for analysis. This bias for low frequencies and/or broad tuning is consistent with our previous studies in primate IC (Groh et al, 2003;Porter et al, 2006). As we noted previously (Porter et al, 2006), a possible explanation for this pattern comes from various studies that have found asymmetries in frequency tuning curves: the cutoff for high frequencies tends to be sharper than that for low frequencies (mouse IC, Egorova et al, 2001;Hage and Ehret, 2003;Yan et al, 2005; cat primary auditory cortex, Sutter, 2000; mouse auditory nerve fibers, Taberner and Liberman, 2005).…”
Section: Methodssupporting
confidence: 91%
“…Neurons responsive only to high frequencies were too rare (one neuron) to include as a separate category for analysis. This bias for low frequencies and/or broad tuning is consistent with our previous studies in primate IC (Groh et al, 2003;Porter et al, 2006). As we noted previously (Porter et al, 2006), a possible explanation for this pattern comes from various studies that have found asymmetries in frequency tuning curves: the cutoff for high frequencies tends to be sharper than that for low frequencies (mouse IC, Egorova et al, 2001;Hage and Ehret, 2003;Yan et al, 2005; cat primary auditory cortex, Sutter, 2000; mouse auditory nerve fibers, Taberner and Liberman, 2005).…”
Section: Methodssupporting
confidence: 91%
“…We based this simple model on the observations that, within the measurement range of azimuths (Ϯ30°) and intensities (40 -60 dB SPL), (1) typical responses to soundsource azimuth were monotonic for contralateral azimuths (Figs. 3, 4) (Groh et al, 2003), (2) the activity of the majority of cells (ϳ70%) tested in the sound-level paradigm (see Materials and Methods) depended monotonically on absolute sound intensity (Fig. 1b), and (3) some neurons had a monotonic sensitivity to changes in sound-source elevation, too.…”
Section: Systematic Sensitivity To 2d Sound Position and Sound Levelmentioning
confidence: 91%
“…The spatial tuning of auditory neurons in the mammalian SC varies with eye position Sparks, 1984, 1987;Hartline et al, 1995;Peck et al, 1995), suggesting that the initial head-centered auditory input has been transformed into oculocentric coordinates. Recently, also IC neurons were reported to be modulated by eye position and sound location in the horizontal plane (Groh et al, 2001(Groh et al, , 2003. These cells were proposed to form an intermediate stage in this coordinate transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The inferior colliculus (IC) is at the core of the ascending auditory pathway, receiving converging inputs from all auditory brainstem nuclei, and is thought to encode the spectral and temporal features of sounds, and of sound locations (Knudsen and Konishi, 1978;Schreiner and Langner, 1997;Groh et al, 2003;Zwiers et al, 2004;Ehret and Schreiner, 2005;Palmer and Kuwada, 2005;Rees and Langner, 2005). It constitutes an obligatory relay between auditory brainstem and cortex and with the midbrain superior colliculus (SC), which is crucial for rapid orienting (Robinson, 1972;Sparks, 1986).…”
Section: Introductionmentioning
confidence: 99%